2016
DOI: 10.1111/1440-1681.12627
|View full text |Cite
|
Sign up to set email alerts
|

Emodin ameliorates acute lung injury induced by severe acute pancreatitis through the up‐regulated expressions of AQP1 and AQP5 in lung

Abstract: The present study investigates the ameliorating effects of emodin on acute lung injury (ALI) induced by severe acute pancreatitis (SAP). An ALI rat model was constructed by sodium ursodeoxycholate and they were divided into four groups: SHAM, ALI, emodin and dexamethasone (DEX) (n=24 per group). Blood samples and lung tissues were collected 6, 12 and 24 hours after the induction of SAP-associated ALI. Lung wet/dry ratio, blood gases, serum amylase and tumor necrosis factor-α (TNF-α) were measured at each time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
(56 reference statements)
4
24
0
Order By: Relevance
“…Aquaporin-1 (AQP1) is protein that functioned as water transport across cell membranes that mainly expressed in alveolus capillary endothelial cells. A number of studies have shown that AQP1 might play an important role in the pathogenesis of ALI, and the decreased lung AQP1 expression was closely related to the development of ALI, while the upregulated the expression of AQP1 could ameliorate ALI [ 7 , 8 ].…”
Section: Instructionmentioning
confidence: 99%
“…Aquaporin-1 (AQP1) is protein that functioned as water transport across cell membranes that mainly expressed in alveolus capillary endothelial cells. A number of studies have shown that AQP1 might play an important role in the pathogenesis of ALI, and the decreased lung AQP1 expression was closely related to the development of ALI, while the upregulated the expression of AQP1 could ameliorate ALI [ 7 , 8 ].…”
Section: Instructionmentioning
confidence: 99%
“…Emodin has a protective effect in pancreatitis-associated secondary organ damage (Wang et al, 2007; Ning et al, 2009; Xia et al, 2010; Xu et al, 2016), which is both a common serious SAP complication and a main cause of death. Pancreatitis-associated lung injury occurs as a consequence of significant pulmonary hyperemia, edema, and inflammatory infiltration in the lung tissues.…”
Section: Pleiotropic Natural Productsmentioning
confidence: 99%
“…Although the strategies in prevention and treatments have been improved, ALI still causes more than 50% of deaths in SAP (Bhatia, 2002). Emodin attenuates pulmonary edema and enhances alveolar epithelial barrier function by up-regulating the expression of claudin-4, claudin-5, occludin, AQP1, and AQP5 in lung tissue samples from rats with SAP-induced ALI (Xia et al, 2010; Xu et al, 2016). Several in vivo investigations have proposed that emodin can prevent the translocation of bacteria and endotoxins and promote the recovery of intestinal barrier function via inhibiting the intestinal mucosa cell apoptosis and up-regulating the serum leptin content (Ning et al, 2009).…”
Section: Pleiotropic Natural Productsmentioning
confidence: 99%
“…Matsuda et al ( 33 ) demonstrated that FK866 protects against ALI in C57BL/6J mice subjected to intestinal ischemia and reperfusion injury. Emodin has previously been reported to be effective in SAP treatment ( 34 ); however, the underlying mechanism remains unclear. The present study indicated that emodin and FK866 significantly ameliorated histopathological alterations induced by SAP-associated ALI in the lung and pancreatic tissues, as determined by HE staining.…”
Section: Discussionmentioning
confidence: 99%